Adaptive Change Detection of the temperature pattern of the face for identifying deceit - Satpathi, Saswata; Bagchi, Sourav; Routray, Aurobinda; Sarathi Satpathi, Partha; Dash, Ritwik (IECON 2021 – 47th Annual Conference of the IEEE Industrial Electronics Society, 2021)
Lie-detection test is fast becoming a defacto standard for the police department to testify the accused. Till now polygraph test remains the gold standard for the purpose. This test is considered to be invasive, time consuming and requires an expert opinion. In this paper we propose alternative non invasive methods based on portable and hidden thermal imaging to detect deceit and falsehood. The major constraint in this research is the availability of proper database emulating deceit. In the present study a real life database has been created using a mock experiment on human subjects. The experiment has been conducted at a government hospital where the subjects have been invited under the plea of health checkup. The subjects are asked to be alone and have been tempted to pick up currency notes appearing to be carelessly dropped on the floor. Subsequently during interrogation some of them lied. During this interrogation their facial thermal video have been captured with a hidden thermal camera. These experiments have been conducted with prior approval of the ethical committee of the hospital. The temperature of the forehead and periorbital region are analyzed. It is observed that there are remarkable changes in the temperature profile in these two areas. Different models have been used to find out the difference between thermal video sequence for persons lying and not lying.